IOS, Company Characteristics and Board of Commissioners’s Effect on Earnings Quality with Intervening Variable Earnings Persistence - Khasanah, Hidayatul; Khafid, Muhammad (Universitas Negeri Semarang, 2020)
This study aims to examine the effect of investment opportunity set, company characteristics and board of commissioners on earnings quality with intervening variable earnings persistence. The population is manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2015-2017 periods which consist of 156 companies. The research sample of 66 companies was obtained using purposive sampling method, so that a total of 198 units of analysis were obtained. Of the total unit analysis, outlier data was reduced by 85 data then the final total unit of analysis is 113 data. This study uses descriptive statistical analysis technique and path analysis. The results shows that IOS, board of commissioners and earnings persistence do not affect the earnings quality. Liquidity and capital structure have a significant negative effect on earnings quality. The board of commissioners does not affect the earnings persistence. The Sobel Test results show that earnings persistence is not able to mediate the influence of the board of commissioners on earnings quality. The conclusion of the study is liquidity and capital structure have a significant negative effect on earnings quality. This is a negative signal because management is considered unable to maintain the stability of the company’s condition.